Metacognitive Reading Strategy Awareness and Reading Performance of Vocational Lecturers - Ester Widawati Tedjo; Susana Teopilus; Tuti Hartani; Eric Sulindra (VELES Voices of English Language Education Society, 2022)
In education, the functions of reading, among others, are to access knowledge, to synthesize information, to evaluate arguments, and to learn new subjects. It is believed that successful readers employ various and proper reading strategies to comprehend a text. To examine the use of the metacognitive strategies in academic reading comprehension, this study investigates the reading performance and the major reading strategies of twenty-five vocational Indonesian lecturers from various institutions as the research respondents. Two research instruments were used: Reading Comprehension Test to obtain the data of their reading performance, and Survey of Reading Strategies (SORS) to identify their preferred reading strategies. The research finding indicates that the respondents had varied levels of English reading performance.  The result also shows that out of the three sub-categories of metacognitive reading strategies, problem-solving strategy was the most frequently used strategy, followed by global strategy and support strategy respectively. Further statistical calculation, however, proves that there was no significant difference in the overall and the three sub-categories of metacognitive reading strategy use between the high and low achievers. There is no significant relationship between the metacognitive reading strategies and reading performance of the participants.